Observations on the development and code of the pre-elegiac paraklausithuron. - Cummings, Michael S. (University of Ottawa (Canada), 1997)
This dissertation surveys and analyzes the development of the Greek and Latin paraklausithuron (paraclausithyron) from its earliest origins through to Horace, but omits detailed discussion of Tibullus, Propertius, and Ovid. It examines not only true paraklausithura, the actual songs or speeches of excluded lovers at their beloveds' doors, but also paraklausithuric situations, where reference is made to a paraklausithuron or to a situation in which a paraklausithuron can easily be presumed to have been sung or said. The survey occupies Chapters 2 and 3 and shows that the paraklausithuron was more popular and pervasive than has been previously recognized. In Chapter 2, paraklausithuric passages are identified in early Greek lyric; it is suggested that Gnesippus was a possible major early influence on the development of the literary paraklausithuron; paraklausithuric parodies are found as early as Aristophanes. Other authors discussed in depth include Euripides and Theocritus. Chapter 3 surveys the paraklausithuron from Plautus through Lucretius, Catullus, and Horace. Throughout, the occurrence and manipulation of topoi are noted and discussed briefly. For the more important topoi, cross-listings are given for occurrences in other paraklausithura. Chapter 1 analyses and defines what is meant by the word "paraklausithuron", supports its utility against the word "komos", states this paper's definitions of "genre" and "topoi", and discusses the connection between the pasaklausithuron and the komos. The survey of the genre before Latin elegy is followed in Chapter 4 by an analysis of several of the most prominent aspects of the relationship between paraklausithura before and in Latin elegy. The identity and status of the paraklausithuric beloved is discussed first, followed by some of the possible religious implications of Greek versus Roman paraklausithura. Finally, by using primary sources from other cultures of antiquity, it is shown that the continued popularity of the paraklausithuron is due to the paraklausithuric situation's essential grounding in reality. Appendix 1 provides a listing, with texts, of paraklausithuric passages after Latin elegy. Appendix 2 contains a word list extracted from the texts presented in Chapters 2 and 3, and Appendix 1.
Keywords: Literature, Classical.